Early Resistance of Non-virulent Mycobacterial Infection in C57BL/6 Mice Is Associated With Rapid Up-Regulation of Antimicrobial Cathelicidin Camp - Adam, Lucille; López-González, Moisés; Björk, Albin; Pålsson, Sandra; Poux, Candice; Wahren-Herlenius, Marie; Fernández, Carmen; Spetz, Anna-Lena (Frontiers in Immunology, 2018)
Early clearance of tuberculosis is the successful eradication of inhaled bacteria before the development of an adaptive immune response. We previously showed, by utilizing a non-virulent mycobacteria infection model, that C57BL/6 mice are more efficient than BALB/c in their control of bacterial growth in the lungs during the first weeks of the infection. Here, we assessed early (within one-three days) innate immune events locally in the lungs to identify factors that may contribute to the control of non-virulent mycobacterial burden. We confirmed that C57BL/6 mice are more resistant to infection compared with BALB/c after intranasal inoculation with mycobacterium. Transcriptomic analyses revealed a remarkably silent signature in C57BL/6 mice despite effective control of bacterial growth. In contrast, BALB/c mice up-regulated genes associated with neutrophil and myeloid cell chemotaxis and migration. Flow cytometry analyses corroborated the transcriptomic analyses and demonstrated influx of both neutrophil and myeloid cell populations in BALB/c mice, while these did not increase in C57BL/6 mice. We further detected increased release of TNF-α from BALB/c lung cells but limited release from C57BL/6-derived cells. However, C57BL/6 mice showed a marked early up-regulation of the Camp gene, encoding the cathelicidin CRAMP peptide, post-mycobacterial exposure. CRAMP (LL-37 in human) expression in the lungs was confirmed using immunofluorescence staining. Altogether, these findings show that C57BL/6 mice can clear the mycobacterial infection early and that this early control is associated with high CRAMP expression in the lungs without concomitant influx of immune cells. The role of CRAMP/LL-37 during mycobacterial infection may be relevant for novel protective strategies, and warrants further studies of human cohorts.